Study: Impact of Agile on Current IT Scenario - Singhal, Anuradha; Chaner, Tarun; Gupta, Richa (International Journal of Computer Sciences and Engineering, 2014)
The present research paper majorly discusses with regard to various issues related to agile software development approach in related to changes mande in diverse background.